HUBUNGAN LITERASI SAINS DENGAN KETERAMPILAN BERPIKIR KRITIS SISWA PADA MATERI IKATAN KIMIA - Yara Dayelma; Zona Octarya; Fitri Refelita (JEDCHEM (JOURNAL EDUCATION AND CHEMISTRY), 2019)
Abstract This research aimed at knowing and describing the correlation between scientific literacy and student critical thinking skill on Chemical Bond lesson. The research method was Quantitative Descriptive with Correlation Hypothesis testing. This research was administered at Vocational High School of Telkom Pekanbaru. The subjects of this research were the eleventh-grade students. The objects of this research were scientific literacy and student critical thinking skill on Chemical Bond lesson. The instruments of collecting the data were Chemical Bond questions based on scientific literacy indicators and critical thinking skill. The questions and questionnaire were stated worthy, if they passed valid aspects. The validity could be seen from validity result by using validation sheet. The technique of analyzing the data was Product Moment Correlation with SPSS 21.0 program. Based on the research findings, it was obtained that there was a significant difference between scientific literacy and student critical thinking skill on Chemical Bond lesson at Vocational High School of Telkom Pekanbaru. The Hypothesis was analyzed by using Pearson Product Moment Correlation with α that was 0.05. The correlation coefficient was 0.910 with probability that was 0.000. It meant that there was a positive correlation between scientific literacy and student critical thinking skill on Chemical Bond lesson. Keywords: Scientific Literacy, Critical Thinking Skill, Chemical Bond